Preserving the Mandi Safar Tradition to Foster Social Caring: A Case Study in South Halmahera - Rahmansah, Esti; Noe, Wahyudin; Sawaludin, Sawaludin; Riyanto, Andra Ade; Hasyim, Rustam (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
The Mandi Safar tradition has been an integral part of the cultural landscape in Baru village, located in the Obi subdistrict of South Halmahera regency. This ritual symbolizes self-purification through immersion in the river, representing a quest for divine protection and the desire to be spared from calamities and misfortunes. Nevertheless, some community members perceive this practice as a bid'ah, or innovation, that contradicts Islamic principles. Despite these differing views, the researcher identifies that the Mandi Safar tradition is valued by many as it significantly strengthens social bonds among villagers.This study aims to provide a comprehensive description of the efforts undertaken by the Baru village community to preserve the Mandi Safar tradition as a means to cultivate social care and solidarity among its citizens. Employing a qualitative research design with a case study approach, the findings reveal that the Mandi Safar tradition is executed in two key stages: (a) the Preparation stage, which entails gathering necessary materials such as paper, pencils, banana leaves, coconut leaves, and food; and (b) the Execution stage, which encompasses the journey to the ritual site, recitation of prayers, communal meals, and the Mandi Safar ritual itself.The Mandi Safar tradition embodies essential social values, including togetherness, affection, and harmony. These values play a crucial role in reinforcing kinship ties within the community and fostering a spirit of social caring among villagers. This study highlights the enduring significance of the Mandi Safar tradition in enhancing communal identity and social cohesion within the Baru village community.